Analisis Isi Pesan Dakwah Dalam Lirik Lagu "Dengan Nafasmu" Group Band Ungu - Arianto; Idmar Wijaya; Muhammad Zainuddin Nawi (AL-MUNAWWIR: Jurnal Komunikasi, Pendidikan, & Syari'ah, 2026)
Da'wah through music or song is nothing new; it has been practiced by many bands in Indonesia, including Ungu, which has released numerous religious songs, one of which is "Dengan Nafasmu." Therefore, the research questions are: 1. What are the lyrics of Ungu's song "Dengan Nafasmu"? 2. What are the da'wah messages contained in Ungu's lyrics? 3. What da'wah values are contained in these lyrics? This research includes a literature review with a descriptive qualitative approach, employing Ferdinand De Saussure's semiotic method. Data were collected through documentation and analyzed using content analysis. The results show that the lyrics of Ungu's song "Dengan Nafasmu" convey Islamic messages. The purpose of this study is to explain the Islamic messages contained in Ungu's songs. Each song contains messages such as repentance, gratitude, regret, trust in God, and answered prayers. Islamic messages in song lyrics were analyzed by dividing them into three categories: messages of faith (aqidah), messages of sharia (syariah), and messages of morality (akhlak).